Updated practice guidelines for the diagnosis and management of aspergillosis: challenges and opportunities - Alevizakos, Michail; Farmakiotis, Dimitrios; Mylonakis, Eleftherios (Journal of Thoracic Disease, 2016)
The Aspergillus genus of fungi is associated with a broad range of diseases, from severe invasive infections in immunocompromised hosts, to semi-invasive, to chronic disease. Invasive aspergillosis in particular constitutes the most common fungal infection among hematopoietic stem cell transplant (HSCT) recipients and the second-most common fungal infection among solid organ transplant recipients (1), with associated mortality rates that exceed 50% (1,2). The new IDSA guidelines (3) provide a valuable tool concerning prevention, diagnosis and management of these diseases, building upon the previous version (4), with the incorporation of new clinical data. Thus, they provide a useful, up-to-date scaffold to assist in clinical decision-making.